THE EFFECT OF E-VOUCHER AND DELIVERY RATE TOWARD FOOD PURCHASING DECISIONS VIA GRAB FOOD : (Case study on students of Muhammadiyah Jambi University) - Sesraria Yuvanda; Deby Aisyah Rj Nur (Journal of Business Studies and Management Review, 2021)
This research aims to analyze the effect of e-voucher and delivery rates toward food purchasing decisions of service users via Grab food. The analysis model used in this research was the multiple regression model. The respondents of this research are the students of the Muhammadiyah Jambi University. The result showed a significant influence between e-voucher and delivery rate provided by Grabfood toward food purchasing decisions of their users.